2004
DOI: 10.1038/sj.bjp.0705756
|View full text |Cite
|
Sign up to set email alerts
|

Thromboxane receptor stimulation associated with loss of SKCa activity and reduced EDHF responses in the rat isolated mesenteric artery

Abstract: 1 The possibility that thromboxane (TXA 2 ) receptor stimulation causes differential block of the SK Ca and IK Ca channels which underlie EDHF-mediated vascular smooth muscle hyperpolarization and relaxation was investigated in the rat isolated mesenteric artery. 2 Acetylcholine (30 nM-3 mM ACh) or cyclopiazonic acid (10 mM CPA, SERCA inhibitor) were used to stimulate EDHF-evoked smooth muscle hyperpolarization. In each case, this led to maximal hyperpolarization of around 20 mV, which was sensitive to block w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
36
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 31 publications
5
36
0
1
Order By: Relevance
“…It is possible that the drug used to increase the tone of the preparation influences the release and/or smooth muscle effects of endothelium-derived factors. Moreover, U46619 has been found to cause marked inhibition of acetylcholine relaxation in mesenteric arteries in the presence of NOS blockade (Plane and Garland 1996), probably by inhibition of the small-conductance calciumactivated K þ channel, which is involved in EDHF-type relaxation (Crane and Garland 2004). However, in the present study only two to three contractions to U46619 were performed, and a comparison of the first and second concentration-response curves showed that flow-and acetylcholine-induced vasodilatations were unaltered.…”
Section: Discussionmentioning
confidence: 49%
“…It is possible that the drug used to increase the tone of the preparation influences the release and/or smooth muscle effects of endothelium-derived factors. Moreover, U46619 has been found to cause marked inhibition of acetylcholine relaxation in mesenteric arteries in the presence of NOS blockade (Plane and Garland 1996), probably by inhibition of the small-conductance calciumactivated K þ channel, which is involved in EDHF-type relaxation (Crane and Garland 2004). However, in the present study only two to three contractions to U46619 were performed, and a comparison of the first and second concentration-response curves showed that flow-and acetylcholine-induced vasodilatations were unaltered.…”
Section: Discussionmentioning
confidence: 49%
“…This was proven to be true with the further development of the IK Ca inhibitors TRAM39 and TRAM34 (Wulff et al, 2000(Wulff et al, , 2001, which clarified a role of these channels in the EDH-mediated relaxation (Crane et al, 2003;Hinton and Langton, 2003). In parallel, IK Ca channel openers such as 1-ethyl-2-benzimidazolinone (1-EBIO) or SK Ca openers (riluzole) were able to reproduce the EDH induced by acetylcholine (Edwards et al, 1999a,b;Walker et al, 2001;Crane and Garland, 2004). These pharmacological studies led to the conclusion that the hyperpolarization observed in the EDH pathway reflects the activation of two potassium channels, IK Ca and SK Ca , which was a key step in our understanding of the EDH-mediated response.…”
Section: B Potassium and Calcium Channels: A Case For The Endotheliumentioning
confidence: 86%
“…Especially the latter was shown to interfere with EDHF signaling in a negative fashion. 25 However, the loss of K Ca 3.1 reduced the overall endothelium-dependent dilation in the carotid artery. This reduction was not caused by an attenuation of the NO-mediated part of the response because inhibition of NO synthase was equally effective in both genotypes.…”
Section: Discussionmentioning
confidence: 99%